2018
DOI: 10.7705/biomedica.v38i0.3904
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and comorbidities in urban areas in Argentina. A gender and age perspective

Abstract: This study will help recognize tuberculosis patients' characteristics and comorbidities influencing the development and evolution of the disease from an age and gender perspective to enable the development of social and community-based strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…The risk of tuberculosis is higher in patients aged below 50 and above 70 [8]. Previously, the incidence of tuberculosis has been reported to be higher in patients aged 20-24 years [9]. In our study, the patients' ages were very variable in both groups but the patients with hemoptysis were younger than those without hemoptysis.…”
Section: Discussioncontrasting
confidence: 37%
“…The risk of tuberculosis is higher in patients aged below 50 and above 70 [8]. Previously, the incidence of tuberculosis has been reported to be higher in patients aged 20-24 years [9]. In our study, the patients' ages were very variable in both groups but the patients with hemoptysis were younger than those without hemoptysis.…”
Section: Discussioncontrasting
confidence: 37%
“…The study aimed to describe the temporal trend of tuberculosis cases according to gender and age group and to make predictions considering the current context in an endemic municipality of northeast Brazil. The study also showed a curious fact, that is, although tuberculosis most commonly affects men of the economically active and older adult age groups, there was a high incidence of the disease in women in the 15 to 59 years age group, an unusual phenomenon, compared with other studies carried out in Brazil and internationally [15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 64%
“…The previous studies found that some characteristic factors were not related to the hepatotoxic effect. The age, gender alcohol intake, and body mass index (BMI) did not have any relationship with hepatotoxic effects [ 17 , 18 ]. Another study explained that women might be at risk for TB because a patriarchal culture is common in Indonesian society; therefore, men have better health than women.…”
Section: Discussionmentioning
confidence: 99%
“…It will aggravate the infectious disease, making nutritional status the major cause of treatment failure in TB patients. Furthermore, malnutrition and TB are two interconnected problems in which malnutrition can impact immune system deterioration and make the affected people's immune systems more susceptible to TB infection than healthy people's immune systems [ 18 , 23 ]. TB is often interconnected with poverty, malnutrition, hygiene, overcrowding, and lack of knowledge [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation